The Effect of Interactive Learning Media on Improving Students' Critical Thinking Skills - Arni, Yusni; Safitri, Yepi; Trisna, Fhidia; Manurung, Elida Smita (ALACRITY : Journal of Education, 2024)
This study was conducted with the aim of studying “the effect of interactive learning media on improving students' critical thinking skills”. This study uses variable (X) interactive learning media and variable (Y) improvement of students' thinking skills. In this study, quantitative research techniques were used, with experimental research methods, namely quasi experimental design. This research used Nonequivalent Control Group design. The learning design in this study is Pretest, Treatmen, and Posttest. Data collection in this study was in the form of tests given to students and documentation. While the validation of the instrument was tested using the content validation test, the construct validation and reliability. Data analysis techniques aim to collect information from all respondents or other data sources using data analysis techniques in the form of normality tests using the Kolmogorov-Smirnov formula, Levene Statistics homogeneity test, and Independent Sample T-Test (t-test) hypothesis testing. The normality results of the pretest or initial ability are 0.200 which means that it is normally distributed. Then the experimental posttest gets a sig value. 0.200 is also normally distributed. The significance value of the homogeneity test is 0.101> 0.05 the data is declared homogeneous. Significant findings (2-tailed), assessed at 0.000 < 0.05. If the significant value (2-tailed) <0.05 then Ha is approved and Ho is rejected in accordance with the decision-making criteria. Based on the data analysis and hypothesis testing that has been done, it can be concluded that there is an "effect of interactive learning media on improving students' critical thinking skills".